Analysis Of Public Policy Process In The Context Of Serang City Development - Eli Apud (Journal of Politica Governo, 2024)
Serang City as the capital of Banten Province continues to grow rapidly. Development in various fields continues to be carried out to improve the welfare of the community. However, the development process cannot be separated from various problems, one of which is related to the public policy process. This research aims to analyse the public policy process in the context of the development of Serang City. The analysis is conducted on the three main stages of public policy, namely agenda setting, formulation, implementation, and evaluation. The results show that the public policy process in Serang City still has some weaknesses, such as the lack of community participation, weak coordination between SKPD, and not optimal evaluation system. Based on the research results, several steps are recommended to improve the public policy process in Serang City, such as increasing community participation, strengthening coordination between SKPD, and improving the evaluation system.